2022
DOI: 10.31332/lifalah.v6i2.2994
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Halal Certification: Its Effect on Interest in Buying Traditional Food

Abstract: This study aims to determine (1)—the influence of religiosity on the interest in buying traditional food of sate bandeng. (2). The effect of halal certification on the interest in buying traditional food of sate bandeng. And (3). The impact of religiosity and halal certification on interest in buying traditional food of sate bandeng. This research is the millennial consumers of traditional food of Sate Bandeng Kang Cepi Kaujon, Serang City, Banten Province. The research method used is quantitative. Methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
7
0
3
Order By: Relevance
“…Research results (Astuti et al, 2020) concluded that the effect of the halal label on increasing sales turnover was very significant. Research result (Najmudin, 2021) shows that halal certification affects buying interest in traditional Sate Bandung food, which indirectly affects the level of sales.…”
Section: Hypothesis Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Research results (Astuti et al, 2020) concluded that the effect of the halal label on increasing sales turnover was very significant. Research result (Najmudin, 2021) shows that halal certification affects buying interest in traditional Sate Bandung food, which indirectly affects the level of sales.…”
Section: Hypothesis Developmentmentioning
confidence: 96%
“…Halal certification is not only focused on the raw materials that are included in the product but also includes the "tayyib" criteria applied in every aspect of production. A halal certificate according to (Basri & Kurniawati, 2019) (Najmudin, 2021) is a document issued by a Legal Religious Institution stating that the product complies with Islamic law and can be used by Muslims. Halal labeling indicators are halal labels printed on product packaging, halal composition listed on product packaging, and trust in product halalness (Andriansyah et al, 2019).…”
Section: Literature Review Halal Certificationmentioning
confidence: 99%
“…Secara eksternal, agama dinyatakan dengan afiliasi agama, layanan ibadah, dan keanggotaan dalam komunitas beragama atau sekedar menghadiri acara keagamaan (Basri & Kurniawati, 2019). Menurut Jalaludin, (2010) seperti yang dikutip (Najmudin & Syihabudin, 2022) religiusitas dapat didefinisikan sebagai suatu keadaan yang ada dalam diri individu yang mendorongnya untuk bertingkah laku sesuai dengan kadar ketaatannya terhadap agama. Di samping itu, Religiusitas dapat juga dikatakan sebagai perwujudan ketaatan beragama dalam keyakinan, pola pikir dan perilaku seseorang dalam mengamalkan rukun Islam yang ketiga (Setiawan, 2017).…”
Section: Pendahuluanunclassified
“…Orang-orang dengan tingkat religiusitas yang lebih tinggi secara signifikan lebih mungkin merasakan hubungan yang lebih besar dengan alam semesta daripada rekan-rekan mereka dengan tingkat religiusitas yang lebih rendah (Anggraini & Dewanti, 2020). Menurut (Ma'zumi et al, 2017) seperti yang dikutip (Najmudin & Syihabudin, 2022) mengemukakan bahwa Religiusitas dapat diukur dengan lima indikator, yaitu (1) Keyakinan ideologis, (2) Praktik keagamaan, (3) Pengalaman religious, (4) Pengetahuan agama, dan (5) konsekuensi.…”
Section: Pendahuluanunclassified
“…Minat menurutMappiare (2000) dalam(Nur & Zulfahmi, 2018) (S Najmudin, 2021). adalah suatu perangkat mental yang terdiri dari suatu campuran dari peresaan, harapan, pendirian, prasangka, rasa takut atau kecenderungankecenderungan lain yang mengarahkan individu kepada suatu pilihan tertentu.Minat adalah kecenderungan untuk menyampaikan perhatian dan bertindak terhadap orang, aktivitas, atau situasi disertai dengan perasaan cinta(Najmudin & Shihabudin, 2022).…”
unclassified